Analisis Realissai Anggaran Belanja Berdasarkan Standar Akuntansi Pemerintah di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Buleleng pada Periode 2018- 2021 - Ni Kadek Vina Suarsini; I Gede Agus Pratama Yudantara , S.E.,M.SA. (Universitas Pendidikan Ganesha, 2024)
This study aims to find out how to analyze the Expenditure Budget Realization in the Buleleng Regency Disdukcapil for the period of 2018-2021 and to find out whether there are obstacles in the preparation of the expenditure budget realization based on Government Accounting Standards if there is any way the Buleleng Regency Disdukcapil overcomes these obstacles. In this study, a quantitative descriptive method was carried out with the method of collecting data from observation, interviews, and documentation. Results of this study 1. Analysis of the realization of the 2018-2019 budget experienced good growth but in 2020 it decreased, but in 2021 it increased due to an increase and decrease in the budget due to several retired employees, and also budget cuts due to COVID 19. 2. The preparation of the realization of the expenditure budget in accordance with the SAK does not have too big obstacles, obstacles faced such as, the cash budget and also the lack of support from fund sources, network constraints that often errors, SIPD that is not perfect so that the preparation process is hampered.